3HE DISTRIBUTION IN THE LUNAR REGOLITH CORE TAKEN BY THE LUNA 24 UNMANNED SPACECRAFT - Galimov E.M.; Anufriev G.S. (My University, 2007)
The thermonuclear reaction with the application of 3He is highly efficient and ecologically unique. In contrast to fission reactions and thermonuclear synthesis with the participation of deuterium and tritium (D + T), which are accompanied by the release of neutrons, the reaction D + 3He = 4He (3.67 MeV) + p (14.68 MeV) proceeds with the release of protons. The neutron flux leads to induced radioactivity of construction materials, their radiation damage, and the necessity of burial of large volumes of radwastes. Since protons are charged particles, they do not penetrate deep into the surrounding materials and induce radioactivity except for the relatively weak influence of the side reaction D + D. Thus, the hazard of radionuclide contamination of the environment drastically diminishes, and the problem of radwaste accumulation is eliminated. The yield of the major portion of thermonuclear energy in the form of protons substantially facilitates engineering solutions of energy utilization.